Effect of Rare Earth Cerium Salt Passivation on the Atmospheric Corrosion Behavior of X70 Carbon Steel - LIU Zhen, LI Shun - ling, PU Xiao - ling, ZHANG Si - yu, YANG Jiang - ping, GAO Xiao - qian, QU Qing (Cailiao Baohu)
Aiming at the corrosive effect of rare earth cerium salt passivation in atmospheric environment, the atmospheric corrosion behavior of conversion coatings prepared by different concentration rare earth cerium salt on X70 carbon steel’s surface was studied by means of weightlessness method, electrochemical impedance spectroscopy (EIS), dynamic potential polarization curve (DP), scanning electron microscope (SEM) and energy spectrometer (EDS) observation. Results showed that the properly cerium salt passivation could effectively improve the corrosion electric potential, reduce the corrosion current density, increase the arc radius of capacitive resistance, and increase the atmospheric corrosion resistance of X70 carbon steel. Furthermore, there was the highest atmospheric corrosion resistance efficiency of X70 carbon steel about 62.3% when rare earth cerium salt concentration was 0.09 g/L. The reason was that the appropriate earth cerium salt addition could increase the densification of passivated film, which formed self - healing repair and consumed a large amount of oxygen in corrosion cathode area.